Dissociation in the phenomenological perspective (in athletes and representatives of extreme careers) - Anastasia S. Vlasik; Alexey V. Korshunov (Национальный психологический журнал, 2015)
This paper attempts to analyze dissociation from the perspective of phenomenology as experience of persons engaged in activities related to high stress (physical and/ or psychological). Dissociation is usually correlated with the so-called reaction fading in life-threatening situations, which along with the reactions of “fight or flight” reveal both in humans and the representatives of the animal world (“fight, flight or freeze”). However, unlike animals humans are often able to act purposefully in dissociative states, or randomly enter them. Specific features and diversity of manifestations of dissociation in humans are determined by the linguistic nature of human consciousness, which is logical to appeal to the philosophers of the phenomenological direction within which consciousness is the subject matter of their research. Based on the concept of Henri Bergson and Gilles Deleuze various manifestations of dissociation are detected: from the grave symptoms of PTSD (the so-called invasion of symptoms) to controlled arbitrarily selected dissociative strategies for athletes. Dissociative experiences by experts of extreme careers are considered: law enforcement officers who participated in missions in «hot spots», and EMERCOM psychologists. Dissociation mechanism in terms of phenomenology is defined. The development and application of adequate diagnostic tools, psychological work with the athletes to regulate the focus of attention during the competition is supposed to contribute to the achievement of a high sports results.